Free cash flows and anomalous returns – the case of Poland - Mizerka, Jacek; Czapiewski, Leszek; Lizińska, Joanna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
This study investigates the performance of the free cash flow portfolio in the period of 2001-2011 in Poland. Firstly, a portfolio of large firms with positive free cash flows, low free cash flow multiples, and low financial leverages was selected. Then it was compared to other firms listed on the Warsaw Stock Exchange. The results were observed in different time periods and exposed to different models. Both buy-and-hold (BHARs) and cumulative abnormal returns (CARs) were estimated. Mean and median buy-and-hold abnormal returns for the free cash flow portfolio were in most of the years much above the averages for other companies. This was also observed for the whole sample period. The difference between the free cash flow portfolio and other companies was significant in economic and statistical terms during market downturns. It may seem plausible that the free cash flow portfolio outperforms other companies, especially during bear markets. However, the free cash flow anomaly was not always robust to different models and statistical tests and dependable in all the years of the sample period. Negative medians for BHARs and the unfavorable comparison of mean CARs between the free and non-free cash flow portfolio were found. This makes the possibility of earning above-average risk adjusted returns on investing in the free-cash-flow portfolio questionable
Argumenta Oeconomica, 2015, Nr 1 (34), s. 77-97
Keywords: market anomaly; free cash flows; Warsaw Stock Exchange